2011
DOI: 10.1007/s12274-011-0177-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface dislocation nucleation mediated deformation and ultrahigh strength in sub-10-nm gold nanowires

Abstract: The plastic deformation and the ultrahigh strength of metals at the nanoscale have been predicted to be controlled by surface dislocation nucleation. In situ quantitative tensile tests on individual <111> single crystalline ultrathin gold nanowires have been performed and significant load drops observed in stress-strain curves suggest the occurrence of such dislocation nucleation. High-resolution transmission electron microscopy (HRTEM) imaging and molecular dynamics simulations demonstrated that plastic defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 29 publications
2
40
0
1
Order By: Relevance
“…Consequently, the onset of plasticity appears in the weakest ligaments, rapidly leading to necking before any global plastic deformation can take place in the rest of the sample. During tensile testing of gold nanowires (10-30 nm diameter), Lu et al [54] observed nucleation of dislocations at the surface, followed by rapid motion across the wire and creation of a necked region prior to failure. Plastic deformation in both nanowires and np-Au ligaments is highly localized and does not manifest itself in the stress-strain curve.…”
Section: Plastic Deformation Behaviourmentioning
confidence: 99%
“…Consequently, the onset of plasticity appears in the weakest ligaments, rapidly leading to necking before any global plastic deformation can take place in the rest of the sample. During tensile testing of gold nanowires (10-30 nm diameter), Lu et al [54] observed nucleation of dislocations at the surface, followed by rapid motion across the wire and creation of a necked region prior to failure. Plastic deformation in both nanowires and np-Au ligaments is highly localized and does not manifest itself in the stress-strain curve.…”
Section: Plastic Deformation Behaviourmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Furthermore, dislocation interactions and multiplications that are typically observed in bulk metals are severely limited in metal nanowires since the nucleated dislocations can easily annihilate at free surfaces. [9][10][11][12][13][14][15][16][36][37][38][39] Several previous studies reported ultra high strength in metal nanowires that approach the theoretical strength as a result of the difficulty in nucleation and multiplication of dislocations within the nanoscale volume of metal nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…A number of interesting phenomena have been observed, including ultrahigh strength, fracture mode transition, and size and strain-rate sensitive mechanical properties. [6][7][8][9] While the size dependence of mechanical properties has been extensively investigated for face-centered cubic (FCC) metals by both experimental and theoretical approaches, [10][11][12][13][14][15][16] the strain-rate effects have not been well studied experimentally. 17 To unravel the relationship between strength and strain rate, the rate-controlling deformation mechanism must be understood.…”
mentioning
confidence: 99%